What are the correlates of childhood undernutrition? An analysis of DHS data from Africa South of the Sahara - Haile, Beliyou; Ru, Yating; Ahn, Hee Eun (International Food Policy Research Institute, 2021)
Despite progresses made over the last several decades, the prevalence of child malnutrition re-mains alarmingly high. About 149 million children under the age of five years old were stunted (too short for their age) in 2018, of which 55% and 39% lived in Asia and Africa, respectively. Malnourished children, especially stunted ones, may never achieve their full cognitive and non-cognitive potential with implications for their educational and labor market performance among other things. Malnutrition results from several interlinked factors operating at child, parental, household, and landscape level such as inadequate maternal nutrition before and during pregnancy and at the time of lactation, suboptimal breastfeeding practices, lack of nutritious complementary foods, and unhealthy living environments. This study analyzes the correlates of child undernutrition in rural Africa South of the Sahara (SSA) – a region with the least progress in tackling undernutrition.